When can display of authenticity at work facilitate coworker interactions? The moderating effect of perception of organizational politics. (January 2023) - Tang, Yipeng; Xu, Erica; Huang, Xu; Pu, Xiaoping
Authenticity has long been held as a virtue. However, is it beneficial for employees to be true to themselves in coworker interactions? Drawing on social penetration theory, we argue that a focal employee's exhibited authenticity at work helps the employee penetrate the interpersonal boundaries of an interacting coworker and as a result, the employee is more likely to be included in this coworker's social circles and receive help from the coworker. Accordingly, we propose a dyadic-level model and test this model in two survey studies using a round-robin design. The results of both studies consistently demonstrated that the focal employee's exhibited authenticity is positively related to help received from the coworker via inclusion in the coworker's social circle. Further, this positive indirect relationship is moderated by the coworker's perception of organizational politics, such that the relationship is weaker when the coworker's perception of organizational politics is high. These findings help advance the understanding of when and how employees can gain relational benefits from displaying authenticity at work.